A perceção de justiça na avaliação do desempenho na Administração Pública e a produtividade - Correia, Pedro Miguel Alves Ribeiro; Mendes, Ireneu de Oliveira; Silva, Sara Raquel dos Santos Rodrigues Manaia (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2019)
Under the reform process in public administration, SIADAP emerges as a new paradigm for performance evaluation, with the intent to improve PA’s management and the performance of their employees. This study aims to assess whether the way in which workers perceive the fairness of the performance evaluation influences their productivity. A theoretical framework on new public management, organizational justice and productivity is presented, followed by a reference to the methodology used, and the results achieved. As a conclusion it is possible to claim that the perceptions of the workers in the Local Government on the variables distributive justice and informational justice have a positive direct impact on their perceptions regarding the satisfaction with the performance evaluation.